2010
DOI: 10.2133/dmpk.dmpk-10-rg-067
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Polymorphisme of FCGRT Encoding FcRn in a Japanese Population and Their Functional Analysis

Abstract: Neonatal Fc receptor (FcRn) plays an important role in regulating IgG homeostasis in the body. Changes in FcRn expression levels or activity caused by genetic polymorphisms of FCGRT, which encodes FcRn, may lead to interindividual differences in pharmacokinetics of therapeutic antibodies. In this study, we sequenced the 5'-flanking region, all exons and their flanking regions of FCGRT from 126 Japanese subjects. Thirty-three genetic variations, including 17 novel ones, were found. Of these, two novel non-synon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 23 publications
2
9
0
Order By: Relevance
“…There were no unique treatment-related adverse events reported in Japanese subjects, and no inhibitors were detected. nese subjects and in other ethnic groups [21][22][23][24] ; however, no functional differences in FcRn due to these polymorphisms were observed, 22 consistent with the similar pharmacokinetic profiles observed. Japanese and non-Japanese subjects in B-LONG was not prespecified, and thus this was a post hoc analysis.…”
Section: Discussionsupporting
confidence: 73%
“…There were no unique treatment-related adverse events reported in Japanese subjects, and no inhibitors were detected. nese subjects and in other ethnic groups [21][22][23][24] ; however, no functional differences in FcRn due to these polymorphisms were observed, 22 consistent with the similar pharmacokinetic profiles observed. Japanese and non-Japanese subjects in B-LONG was not prespecified, and thus this was a post hoc analysis.…”
Section: Discussionsupporting
confidence: 73%
“…Thirty-three genetic variations were found in FCGRT, but the two non-synonymous variations characterized were similar to the wild type in their intracellular localization and antibody recycling efficiencies. 11) The variable number of tandem repeat (VNTR) found in human FCGRT promoter influenced the transcriptional activity of FCGRT in monocytes, but has not shown association with risk for glomerular nephritis or with transfer of IgG from mother to fetus. 12) In the present study, the genetic variants found in cynomolgus and rhesus FCGRT and B2M did not appear to influence the FcRn function.…”
Section: Resultsmentioning
confidence: 99%
“…mAbs against soluble antigens are primarily eliminated by Fc receptor‐mediated clearance, which involves a non‐specific common pathway for endogenous IgG and mAbs via FcRn and FcγR, a process that shows linear pharmacokinetics. Several reports have described ethnic differences in these pathways . For FcRn, genetic polymorphisms of FCGRT were reported to show ethnic differences, as the mean allelic frequency of the variable number of tandem repeats was 0.032 in Japanese individuals versus 0.075 in Caucasians .…”
Section: Ethnic Differences In the Pharmacokinetics Of Monoclonal Antmentioning
confidence: 99%
“…Several reports have described ethnic differences in these pathways . For FcRn, genetic polymorphisms of FCGRT were reported to show ethnic differences, as the mean allelic frequency of the variable number of tandem repeats was 0.032 in Japanese individuals versus 0.075 in Caucasians . However, the impact of these genetic variations on the function of FcRn is yet to be established.…”
Section: Ethnic Differences In the Pharmacokinetics Of Monoclonal Antmentioning
confidence: 99%